PENGARUH METODE FERMENTASI TERHADAP PENINGKATAN KANDUNGAN KIMIA DAN AKTIVITAS FARMAKOLOGI PADA BEBERAPA TANAMAN: Artikel Review - Puspitasari, Melisa; Riyanti, Soraya (Jurnal Buana Farma, 2024)
Fermentation is a process that involves the chemical transformation or breakdown of complex organic substances or other food components into simpler compounds through the action of natural enzymes and fermenting microorganisms. The purpose of this literature review is to explore the impact of fermentation methods on the enhancement of phytochemical content and pharmacological activity in various plants. Journal searches were conducted on Google Scholar, PubMed, and ScienceDirect. The results revealed that fermentation methods can increase the chemical content and pharmacological activity of a plant. Microorganisms that are frequently used in the fermentation process, such as Bacillus subtilis and actobacillus brevis, can increase the total phenol content and enhance antioxidant activity. Factors influencing the fermentation process in improving the chemical content and pharmacological activity of a plant include treatment methods, duration of fermentation (incubation), microorganisms used, and the concentration of inoculum used.